Use of Two Step Small Group Discussion to Enhance Learning of Basic Immunology - Nafiseh Pakravan; Zohreh Ghazivakili; Rouhangiz Norouzinia; Behrooz Pouragha; Zohreh Ghazivakili; Behrooz Pouragha (Kerman University of Medical Sciences, 2015)
Background & Objective: Discussion in small groups is one of the most reliable methods that will lead to a deeper learning This method is based on the active participation of all members of the group The immunology course necessitates thought and connection among the presented content Therefore in this study the efficacy of this method in increasing students understanding of the relationship between the components of the immune system was evaluated   Methods: The course lectures were presented in 12 sessions each lasting 2 hours Then the students were given the opportunity to study for a few days An exam was taken based on the presented content and then the students were divided into groups under the titles of immune system cells The discussion sessions were conducted A second exam was taken after the discussion Scores of pre and postdiscussion in small groups were compared Students satisfaction with this approach was asked orally and through open questions and recorded   Results: A statistically significant increase was observed in students scores after the discussion in small groups compared to before the discussion Among the students 65% believed that this method had a great effect on deep understanding and were willing to repeat this approach Furthermore 82% of students believed that their confidence increased in respect to what they had learned   Conclusion: Small group discussion is a potent educational method because its implementation in 1 session on taught content resulted in an increase in scores The implementation of this method may be difficult for the teacher but this approach has significant effects on student learning behavior